Caracterización clínica del síndrome de takotsubo - Chalan Espinoza, Bryan Anthony (Machala : Universidad Técnica de Machala, 2024)
Introduction: Takotsubo syndrome (TTS), also known as stress cardiomyopathy, constitutes the only reversible cardiac condition, characterized by a transient alteration of left ventricular contractile morphology. TTS occurs most frequently in postmenopausal women, preceded by a triggering event, which may be physical or emotional, which is why the pathophysiology has not yet been determined. TTS clinically simulates an Acute Coronary Syndrome; however, the electrocardiographic, echocardiographic, angiographic, etc. peculiarities allow for an adequate therapeutic approach. Objective: To analyze the clinical characteristics of TTS in the form of presentation of Broken Heart Syndrome and Happy Heart Syndrome. Methodology: A descriptive, documentary study was carried out based on the review of articles from indexed journals within the last 5 years of publication, using PUBMED, SCIELO and Google Scholar databases to differentiate the forms of presentation of Takotsubo Syndrome. Conclusion: The incidence of TTS has been increasing in recent years, due to the stressful (emotional) events to which society is exposed, which have led to TTS being referred to as Broken Heart Syndrome or Happy Heart Syndrome; however, as is evident, clinically they have the same characteristics, with specific peculiarities, such as the form of presentation, age of onset, gender predisposition, complications, and prognosis, which make them receive one or the other classification.
Introducción: El síndrome de Takotsubo (STT), conocido también como miocardiopatía por estrés, constituye la única afección cardiaca reversible, que se caracteriza por una alteración transitoria de la morfología contráctil del ventrículo izquierdo. El STT se presenta con mayor frecuencia en mujeres postmenopáusicas, precedida por un evento desencadenante, que puede ser físico o emocional, este motivo hace que la fisiopatología no esté determinada hasta el momento. El STT, clínicamente simula a un Síndrome Coronario Agudo; sin embargo, las particularidades electrocardiográficas, ecocardiográficas, angiográficas, etc. permiten realizar un abordaje terapéutico adecuado. Objetivo: Analizar las características clínicas del STT en la forma de presentación de Síndrome de Corazón Roto y Síndrome de Corazón Feliz. Metodología: Se realizó un estudio de tipo descriptivo, documental basado en la revisión de artículos de revistas indexadas que se encuentren dentro de los últimos 5 años de publicación, utilizando para ello, bases de datos de PUBMED, SCIELO, Google Académico, para lograr diferenciar las formas de presentación del Síndrome de Takotsubo. Conclusión: El STT presenta incidencia que ha ido en aumento en los últimos años, debido a los eventos estresantes (emocionales) a los que la sociedad está expuesta, que hacen que al STT se le denomine como Síndrome de Corazón Roto o Síndrome de Corazón feliz; sin embargo, como se deja en evidencia, clínicamente presentan las mismas características, siendo particularidades puntuales, como la forma de presentación, edad de aparición, predisposición por género, complicaciones, y pronóstico, las que hacen que reciban una u otra catalogación.
Keywords: SINDROME DE TAKOTSUBO; SINDROME DEL CORAZON ROTO; MIOCARDIOPATIA DE TAKOTSUBO